A Fluid–Structure Interaction Study of Different Bicuspid Aortic Valve Phenotypes Throughout the Cardiac Cycle - Yan, Wentao; Li, Jianming; Wang, Wenshuo; Wei, Lai; Wang, Shengzhang (Frontiers in Physiology, 2021)
The bicuspid aortic valve (BAV) is a congenital malformation of the aortic valve with a variety of structural features. The current research on BAV mainly focuses on the systolic phase, while ignoring the diastolic hemodynamic characteristics and valve mechanics. The purpose of this study is to compare the differences in hemodynamics and mechanical properties of BAV with different phenotypes throughout the cardiac cycle by means of numerical simulation. Based on physiological anatomy, we established an ideal tricuspid aortic valve (TAV) model and six phenotypes of BAV models (including Type 0 a-p、Type 0 lat、Type 1 L-R、Type 1 N-L、Type 1 R-N、Type 2), and simulated the dynamic changes of the aortic valve during the cardiac cycle using the fluid-structure interaction (FSI) method. The morphology of the leaflets, hemodynamic parameters, flow pattern and strain were analyzed. Numerical results showed that the orifice of BAV was similar to an ellipse due to the influence of raphes compared to the approximate circular orifice of TAV. Compared with TAV, the cardiac output (CO) and effective orifice area (EOA) of different BAV phenotypes decreased certain degree, along with the peak velocity and mean pressure difference (∆P) increased both. Among all BAV models, Type 2 exhibited the worst hemodynamic performance. During the systole, obvious asymmetric flow field was observed in BAV aorta, which was related to the orientation of BAV. Higher strain was generated in diastole for BAV models. The study suggests specific differences in the hemodynamic characteristics and valve mechanics of different BAV phenotypes. Certain degrees of aortic stenosis were found for all BAV phenotypes. The eccentric jet flow of different BAV phenotypes may be potentially related to the position of ascending aortic dilation. Besides, the higher strain on leaflets during diastole may accelerate the occurrence of calcification or other pathophysiology processes.